Supervision and Registration of Traditional Medicine Brand in Indonesia - Tjia Siauw Jan; Tri Handayani; Memed Sueb (Nagari Law Review, 2021)
Traditional medicine (herbal medicine, standardized herbal medicine, phytopharmaca (clinical-based herbal medicine), imported traditional medicine) is an ingredient or herb ingredients in the form of plant ingredients, animal ingredients, mineral ingredients, galenic preparations, or a mixture of such ingredients that have been used for treatment for generations, and can be applied by the norms prevailing in the society. This study aims to find out and analyze related to the supervision and registration of traditional medicine brands in Indonesia. This research uses a qualitative method with a normative juridical approach. Data collection techniques are carried out through library studies. It can be concluded that the supervision of traditional medicine brands' registration must be carried out to the maximum by the National Agency of Drug and Food Control (NADFC). This avoids the problems that will arise in the event of the obscurity of the surveillance process. Good and proper supervision must be based on the rule of law because Indonesia recognizes the Law's existe.